2003
DOI: 10.1093/ortho/30.2.155
|View full text |Cite
|
Sign up to set email alerts
|

A Prospective Randomized Clinical Trial to Compare Pre-coated and Non-pre-coated Brackets

Abstract: The clinical failure rate of pre-coated brackets is not significantly lower than conventional non-pre-coated brackets.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
22
1
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 8 publications
0
22
1
1
Order By: Relevance
“…Several models have been used to evaluate and compare different orthodontic bonding materials, including in vitro , ex vivo , and in vivo models 27,10,12. In vivo models are assumed to be the most valid because bond strength is tested in the normal oral environment, which contains a number of parameters that are impossible to reconstruct in an in vitro or ex vivo model.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several models have been used to evaluate and compare different orthodontic bonding materials, including in vitro , ex vivo , and in vivo models 27,10,12. In vivo models are assumed to be the most valid because bond strength is tested in the normal oral environment, which contains a number of parameters that are impossible to reconstruct in an in vitro or ex vivo model.…”
Section: Introductionmentioning
confidence: 99%
“…Precoated brackets have been evaluated in several studies, and these have reported conflicting results 2,3,7,12. One in vitro study found no significant difference between the shear bond strengths of precoated and conventional brackets 2.…”
Section: Introductionmentioning
confidence: 99%
“…Several models have been used to evaluate and compare different orthodontic bonding materials, including in vitro, ex vivo, and in vivo models. [2][3][4][5][6][7]10,12 In vivo models are assumed to be the most valid because bond strength is tested in the normal oral environment, which contains a number of parameters that are impossible to reconstruct in an in vitro or ex vivo model. Some of these factors include the stress arising from an activated arch wire coupled with occlusal loads, extreme pH and temperature variations, and the presence of complex oral micro flora and their by-products.…”
Section: Introductionmentioning
confidence: 99%
“…Precoated brackets have been evaluated in several studies, and these have reported conflicting results. 2,3,7,12 One in vitro study found no significant difference between the shear bond strengths of precoated and conventional brackets. 2 Another in vitro study, however, found that precoated metal brackets exhibited lower bond strength than conventional ones when the same adhesive was used for both.…”
Section: Introductionmentioning
confidence: 99%
“…Por un lado, Wong realizó un estudio in vivo y determinó que ni los brackets APC ni los brackets normales tienen beneficios clínicos uno sobre otro en términos de fuerza adhesiva en los primeros seis meses de tratamiento. Además, se concluyó que la adhesión de los brackets APC no se realiza en un tiempo significativamente menor que la de los brackets convencionales(Wong & Power, 2003). Por otro lado, también otros autores realizaron estudios similares, como Verstrynge et al, quien realizó una comparación clínica del sistema adhesivo de los brackets cerámicos APC y brackets normales con Transbond XT.…”
unclassified